Financial Report Quality and Organizational Commitment in West Java’s Accountability System - Sinaga, Hotdy Rizky Hamonangan; Kustinah, Siti (Jurnal Akuntansi, 2025)
Purpose – The principal objective of this study is to investigate how the quality of financial statements, alongside the stage of organizational commitment, affects the performance accountability system inside of government institutions operating under the auspices of the West Java Provincial Government. Design/methodology/approach – This study adopts a quantitative methodology characterised by both descriptive and associative approaches. The data collection procedure was carried out by means of questionnaires distributed to a specimen comprising 76 employees by the Regional Device Work Units (Satuan Kerja Perangkat Daerah—SKPD) inside of West Java Province. Employing a saturation sampling technique, the study undertook data analysis that included validity and reliability testing as well as multiple linear regression analysis. Findings – the outcomes of the study reveal that the quality of financial statements exerts a favorable effect on the performance accountability system, by the dimensions of relevance and reliability identified as particularly significant factors in this relationship. Additionally, organizational commitment has also been found to favorably affect performance accountability systems, particularly in the dimensions of affective commitment and normative commitment. Collectively, the quality of financial statements and organizational commitment significantly impact the performance accountability system of government institutions. Research limitations/implications – Although the outcomes indicate a favorable impact, the study also reveals that several dimensions inside of budgeting and performance measurement still need improvement. Therefore, it is recommended that local governments focus on enhancing the reliability of financial statements, strengthening long-term employee commitment, and improving performance measurement and evaluation to meet all organizational objectives proportionally. Keywords: Financial Statement Quality, Organizational Commitment, Performance Accountability System, Performance Measurement, West Java Provincial Government